Achieving success through innovation : cases and insights from the hospitality, travel, and tourism industry - Enz, Cathy A., 1956-; Kimes, Sheryl E.; Siguaw, Judy A.; Verma, Rohit; Walsh, Kate.; Withiam, Glenn (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2016)
This book investigates the genesis and success of innovation in the hospitality industry as detailed in over four dozen case studies. In many of the cases, the innovators themselves provide the insights into their innovative inspiration and the lessons learned from the way they brought their ideas to life. The cases include innovations for improved customer service, stronger human resources, and new food service and lodging concepts. While updated technology forms the basis for many of the innovations, some of the cases focus specifically on technology improvements, with a particular focus on the use of technology as a mediator in the service value chain. With the passage of several years, the book shares the outcome of the innovative concepts--most of which continue to operate. The lessons presented will provide you a valuable perspective on success through innovation, whether you are operating in the hospitality industry or another business.
1. The nature of innovation -- 2. Improving the customer experience -- 3. Better human resources for improved operations -- 4. Sustainability innovation -- 5. Applying technology for corporate success -- 6. Innovative restaurant concepts -- 7. Lodging concept innovation -- 8. Strategic intermediation -- 9. Achieving success through innovation -- About the authors -- Index.
Includes bibliographical references and index.
Title from PDF title page (viewed on September 14, 2016).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Hospitality industry -- Management; Tourism -- Management; Technological innovations; customer service; food-service concepts; hospitality innovation; human resources; innovation; innovation strategy; international hotel operation; lodging concepts; technology innovation; Electronic books